Application of channel-belt scaling relationships to early Middle Jurassic source-to-sink system evolution in the southern Junggar Basin. (July 2020) - Li, Ya-nan; Shao, Longyi; Xu, Jie; Hou, Haihai; Tang, Yue; Yuan, Yuan; Zhang, Jiaqiang
Abstract: A wide range of key scaling relationships obtained from modern fluvial systems can be used to estimate the drainage areas in ancient source-to-sink systems. In this study, these relationships are applied to reconstruct source-to-sink systems of the early Middle Jurassic Xishanyao Formation in the southern Junggar Basin where meandering fluvial and deltaic successions are developed. Both the lower channel-belt thickness and the bankfull channel-belt thickness are measured and are used to estimate the scale of drainage systems that were associated with the seven fluvial systems in three sequences (Sequence 1, 2 and 3 in ascending order). The results indicate that the channel-belt thickness had significant variation through time and space. The average values of the bankfull thickness of the seven fluvial systems are translated into drainage area, which range from 63, 000–157, 000 km 2, and the maximum drainage length, which range from 559 to 934 km. The delta volume of the seven fluvial systems range from 2.01 km 3 to 10.35 km 3 . From Sequence 1 to Sequence 3, detrital mineral compositions of sandstones show a gradual change from lithic arkose to feldspathic litharenite. Provenance fields on ternary plots and the characteristics of sandstone components show that the sandstone sources gradually shifted from the southwest-dominated Yilinhabierga Mountains to the southeast-dominated Bogda Mountains. Sediment provenance analysis, together with paleogeographic maps and analysis of sedimentary records, suggests that orogenic building of the Bogda Mountains was responsible for the progressive eastward shifting of the main fluvial channels, and for the modification of drainage areas. The mismatched pattern of channel sizes between the rivers developed in the early Middle Jurassic and in the modern northern Tian Shan front is due to late Cenozoic north-south crustal shortening, which had caused the drainage network reorganization and the evolution of fluvial styles. Our work provides a complete profile of sediment dispersal from source to sink for better understanding of the paleogeographic evolution in the southern Junggar Basin. This source-to-sink approach could also be applicable to other lacustrine basins in China. Highlights: Meandering fluvial deposits are preserved in the southern Junggar Basin. Modern scaling relationships were applied to the Jurassic channel sand bodies. The drainage basin size was scaled with bankfull thickness and delta volume. A large-scale tectonic and drainage reorganization occurred from Sequence 1 to 3. A complete profile of sediment dispersal evolution from source to sink was built.